Extensions Of Multivariate Coefficient Of Variation Control Charts - Ayyoub, Heba Nasr Awwad (2021)
Control charts for monitoring multivariate coefficient of variation (MCV) are applied when the interest is in monitoring the relative multivariate variability to the mean vector of a multivariate process. This thesis proposes an upper-sided variable sampling interval (VSI) exponentially weighted moving average (EWMA) chart to detect upward shifts in the MCV squared (